Introduction to Python programming in finance - Jin, Yuchen (Nanyang Technological University, 2021)
The main purpose of this project is to discover and develop an effective learning methodology for finance students to master Python programming and achieve the best education outcome. The author designed the whole project closely with the content from Nanyang Technological University course AE 8225 to provide finance students with the most suitable and practical exercises. Finance students will have a good understanding of what they have learned from the lecture after completing these projects. The author’s report provides two complete projects that can be used as assignments to cultivate finance students with basic programming skills and improve their ability to analyze and solve problems. Two projects will be covering data analysis on the Yahoo Finance stocks, Python Excel commands, data visualization of trends, and tkinter GUI programming. Each of them is divided into a 6-week assignment. Also, out of the consideration of different students’ programming backgrounds, the report shares some higher-level project topics to stimulate students' interests in learning Python programming.